2016
DOI: 10.1111/bju.13412
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of docetaxel, bevacizumab, lenalidomide and prednisone in patients with metastatic castration‐resistant prostate cancer

Abstract: With appropriate supportive measures, combination angiogenesis inhibition can be safely administered and potentially provide clinical benefit. These hypothesis-generating data would require randomized trials to confirm the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Third, the number of subjects and selection bias in our study are potential factors affecting our assessment of the relationship between ADC and VEGF expression level. Anti‐VEGF therapies in clinical studies have shown some benefits for patients with PCa . According to our results, we can speculate that ADC may be used as a biomarker to assess the treatment response to anti‐VEGF drugs in PCa.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Third, the number of subjects and selection bias in our study are potential factors affecting our assessment of the relationship between ADC and VEGF expression level. Anti‐VEGF therapies in clinical studies have shown some benefits for patients with PCa . According to our results, we can speculate that ADC may be used as a biomarker to assess the treatment response to anti‐VEGF drugs in PCa.…”
Section: Discussionsupporting
confidence: 59%
“…Antiangiogenic treatment has been shown to be effective in inhibiting the progression of some tumors. Many recent trials have found that a combination of VEGF inhibitors may have clinical benefits for patients with PCa, and anti‐VEGF therapies are emerging as promising treatment methods for PCa.…”
Section: Introductionmentioning
confidence: 99%
“…There are several possible explanations for the failure of these trials, including hetereogeneity in patient stages and selection, treatment-related toxicities or activation of resistance mechanism through induction of pro-angiogenic factors [12] , [13] . A recent phase II trial concludes that combination of anti-angiogenics (bevacizumab and lenalidomide⿿though arguably lenalidomide is not a ⿿pure⿿ anti-angiogenic) is able to circumvent the toxicity and may have clinical benefit [14] . Despite the insufficient data for the effectiveness of anti-angiogenic treatment in PCa, the above mentioned studies suggest that further research is required to establish the exact mechanism of regulation of angiogenesis in tumours.…”
Section: Is There a Rationale For Developing Anti-angiogenics In Prosmentioning
confidence: 99%
“…CD8 + T-cells, Foxp3 − CD4 + T-cells, and Tregs were evaluated for levels of expression of immune checkpoint receptors (CTLA-4, PD-1, and TIM-3). CD14 + monocytes were evaluated for HLA-DR expression, and the levels of CD14 + HLA-DR hi monocytes and CD14 + HLA-DR low/neg monocytes were evaluated as described previously 47 . The following monoclonal antibodies were used (all from BioLegend, San Diego, CA, USA): for MDSC analysis, Alexa Fluor 647-CD3 clone OKT3, Alexa Fluor 647-CD56 clone MEM-188, Alexa Fluor 647-CD19 clone HIB19, PE-Cy7-HLA-DR clone L243, PerCP-CD14 clone HCD14, Alexa Fluor 488-CD11b clone ICRF44, PE-CD33 clone WM53, and Pacific Blue-CD40 clone 5C3.…”
Section: Methodsmentioning
confidence: 99%